Optimization Management Communication in Rehabilitation of Disaster Victims: A Review in Kampar Regency - Ekarianto, Ekarianto; Marantika, Abshor (Dinasti Publisher, 2026)
Communication is very important elements in countermeasures disasters, including various aspect like mitigation, preparedness, response emergency, and recovery (Shannon & Weaver, 1949; UNICEF, 2020). In context this, effective communication​ become foundation main for reach system management efficient disaster management. Resilience, speed, and capability for adapt with progress technology become condition absolute in face challenges posed by disasters​ natural disasters​ nature, such as floods, earthquakes earth, and fire, have significant impact​ to community. Impact This No only limited to damage physical, but also includes loss large economic impacts. for example, a disaster floods in Kampar Regency have cause increasing losses​ from year to years. Effective rehabilitation is essential​ for restore life affected communities, and management good communication​ can play a role in increase awareness as well as participation public in the rehabilitation process.